Cephenniini of the Philippines. Part 6. First record of Cephennomicrus Reitter from Mindanao, with three new species (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2024)
Seven nominal species of Cephennomicrus Reitter are currently known to occur in the Philippines: three species have been recorded from Luzon, three from Palawan, and one from Leyte. The occurrence of this genus on Mindanao is reported for the first time, with three new species described: Cm. apoensis sp. n., Cm. candalaganus sp. n., and Cm. talonoensis sp. n. The distribution of Philippine Cephennomicrus species is summarized.